2013
DOI: 10.1007/s10815-013-0108-9
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study to evaluate the effect of hyaluronic acid sperm selection on the intracytoplasmic sperm injection outcome of patients with unexplained infertility having normal semen parameters

Abstract: Purpose Sperm quality plays an important role in determining embryo development and intracytoplasmic sperm injection (ICSI) outcome. Selection of competent sperm based on its ability to bind to hyaluronic acid (HA) has been suggested as one of the methods to assess sperm quality. The aim of the present study was to examine whether injection of HA bound sperm helps in improving outcome in patients undergoing ICSI with unexplained infertility having normal semen parameters. Methods Patients with unexplained infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 20 publications
(26 reference statements)
5
54
2
Order By: Relevance
“…Another recent study did not find any differences in FR, IR, and CPR between ICSI and PICSI patients. The only benefit of injecting HA selected sperm was a lower PLR which consequently translated to a higher LBR, both of which were not statistically significant [Majumdar and Majumdar 2013].…”
Section: Discussionmentioning
confidence: 79%
“…Another recent study did not find any differences in FR, IR, and CPR between ICSI and PICSI patients. The only benefit of injecting HA selected sperm was a lower PLR which consequently translated to a higher LBR, both of which were not statistically significant [Majumdar and Majumdar 2013].…”
Section: Discussionmentioning
confidence: 79%
“…For instance, in the study by Majumdar & Majumdar (2013), the morphologic selection and the HA system techniques were compared in relation to patients with infertility without apparent reason and without associated male factors. Indeed, the results did not show significant differences, but demonstrated a tendency in the reduction of abortion rates in the cases that used the HA system for sperm selection.…”
Section: Discussionmentioning
confidence: 99%
“…Favoring selection of spermatozoa with intact DNA and normal nucleus, HA may be another alternative to optimize ICSI outcome, in fact some studies have shown significant differences (Parmegiani, 2010) while others did not find differences in clinical pregnancy rate or embryo quality (Ménézo & Nicollet, 2004;Majumdar & Majumdar, 2013). We decided to compare the two new methods for sperm selection, patients of PICSI group show clinical pregnancy rate benefits compared to ICSI group (40.4% vs 27.3 %, respectively), but its benefit was inferior to the MACS group (58.1%).…”
Section: Discussionmentioning
confidence: 99%